Pengaruh Profitabilitas, Penerbitan Surat Berharga Syariah, Ukuran Perusahaan dan Leverage Terhadap Islamic Social Reporting pada Bank Umum Syariah Di Indonesia Tahun 2015-2018 - Ade Tri Darma Pertiwi DS; Mahatma Kufepaksi; Muslimin Muslimin (Goodwood Publishing, 2022)
This study aims to determine the effect of profitability, issuance of sharia securities, company size and leverage on Islamic social reporting at Islamic commercial banks in Indonesia of the 2015-2018 period. The population in this study were 13 Islamic commercial banks listed on the Indonesia Stock Exchange for the period 2015-2018. The sample in this study was taken using purposive sampling and obtained as many as 12 sample companies. This research uses quantitative research methods with data analysis techniques, multiple linear regression analysis and descriptive statistics processed with SPSS 19. The results of this study indicate that the issuance of sharia securities and company size variable has a significant positive effect on Islamic social reporting, while the profitability variable and leverage have no effect on the Islamic social reporting in Indonesia for the 2015-2018 period.